Kutluğ Ataman - Çavuş, Metin ([Turkey] : The Institute for the Readjustment of Clocks, 2011)
Double DVD Set contains excerpts from:##- kutlug ataman's semiha b. unplugged, 1997##- Women Who Wear Wigs, 1999##- Never My Soul, 2001##- The 4 Seasons of Veronica Read, 2002##- 99 Names, 2002##- It's a Vicious Circle, 2002##- Twelve, 2004##- Kuba, 2004##- Stefan's Room, 2004##- Paradise, 2006##- Turkish Delight, 2007##- Testimony, 2008##- fff, 2009##- Beggars, 2010## ##and Mesapotamian Dramaturgies:##- The Complete Works of William Shakespeare, 2008##- Colum, 2009##- Dome, 2009##- English as a Second Language, 2009##- Frame, 2009##- Journey to the Moon, 2009##- Pursuit of Happiness, 2009##- Strange Space, 2009
film
Keywords: Ataman, Kutlug; Çavuş, Metin